2012
DOI: 10.2139/ssrn.2020745
|View full text |Cite
|
Sign up to set email alerts
|

Lost in Translation? Teacher Training and Outcomes in High School Economics Classes

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Another study compared teacher characteristics using random effects and fixed effects and found that increasing teachers’ college coursework led to lower student scores on an essay test. This suggests that teachers with more advanced knowledge may be trying to teach at too high a level for high school students and that their knowledge may be “lost in translation” (Valletta et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study compared teacher characteristics using random effects and fixed effects and found that increasing teachers’ college coursework led to lower student scores on an essay test. This suggests that teachers with more advanced knowledge may be trying to teach at too high a level for high school students and that their knowledge may be “lost in translation” (Valletta et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%